2021
DOI: 10.3389/fsurg.2021.691674
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Leiomyoma in a Healthy Middle-Aged Woman: Literature Review and Case Report

Abstract: Introduction: Primary hepatic leiomyoma (PHL) is a rare benign hepatic tumor with unclear pathogenesis. It more commonly occurs in immunosuppressed patients, while only 24 cases have been described among immunocompetent individuals. To date, only one successful preoperative diagnosis of PHL has been achieved.Case Presentation: Here we report a case of PHL in a middle-aged woman with no history of immunosuppression. Preoperative diagnosis of PHL was established using ultrasound-guided fine needle trucut biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Since the first described case in 1926 by Demel et al, there have been less than 50 cases of PHL reported in the medical literature. 7 Among all reported cases, only 24 cases were among immunocompetent patients. 8 PHL diagnostic criteria as described by Hawkins et al require that the tumor in question originates from hepatic mesenchymal tissue and that there are no primary tumors elsewhere in the body including the urogenital organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first described case in 1926 by Demel et al, there have been less than 50 cases of PHL reported in the medical literature. 7 Among all reported cases, only 24 cases were among immunocompetent patients. 8 PHL diagnostic criteria as described by Hawkins et al require that the tumor in question originates from hepatic mesenchymal tissue and that there are no primary tumors elsewhere in the body including the urogenital organs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first described case in 1926 by Demel et al, there have been less than 50 cases of PHL reported in the medical literature. 7 Among all reported cases, only 24 cases were among immunocompetent patients. 8 …”
Section: Discussionmentioning
confidence: 99%